Pengaruh Naungan dan Pupuk NPK terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Br Siregar, Ernawati; Nurbaiti, Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aimed to determine the effect of shade and NPK fertilizer and get the dose of NPK fertilizer at various levels of better shade to the growth of cocoa seedlings. The research was conducted in the experimental station of agriculture faculty of Riau University from June to September 2017. The research was conducted in the form of experiments arranged in a split plot design used a complete random design (RAL) consisting of 2 factors and 3 replications.The main plot is a shade consisting of no shade, 50% shade and 75% shade, sub plot is the dose of NPK fertilizer 0, 2, 4, 6 g/polybag.Data have been statistically analyzed and examined further with using the smallest real difference test (BNT) at 5% level.The outcomes indicated that there is interaction between shade and NPK fertilizer on cocoa leaf area, but no interaction on seedling height, leaf number, stem circumference, root volume, shoot root ratio and dry weight. Giving a of 75% shade have better effect on the parameters of seedling height, leaf number, stem circumference, leaf area, root volume, shoot root ratio and dry weight. The dose of NPK 4 g/polybag fertilizer gave better effect to parameters of seedling height, leaf number, stem circumference, leaf area, shoot root ratio and dry weight. Giving 75% shade with a dose of NPK 4 g fertilizer showed the best treatment on all parameters for the growth of cocoa seedlings.Â Keywords:Cocoa seedlings, shade, NPK fertilizer, growth